Scrollytelling: visualizing voting patterns across members of the Colombian Congress (2018)
Politics has an intrinsic accountability problem: officials are elected to represent the interest of their constituents, but the latter cant be aware with the particulars of the day to day actions of the former, particularly when it involves thousands of votes. This creates a knowledge imbalance that makes political accountability and transparency harder. Congreso Visible (CV) is an organization dedicated to make the day-to-day actions of Congress more visible and accountable. Together weve worked to identify, highlight and visualize insights by turning CVs vast data silos containing years of voting data into a web-based storytelling experience using data visualization